PRODUCTION METHOD OF RENEWABLE ENERGY TOOLS: SMALL SIZED SILICON-BASED SOLAR CELL - Ozgun Boray YURDAKOS (International Journal of Research Science and Management, 2017)
The need for the new sources of energy has been rising progressively considering the growing demand. It is well-known that fossil fuels will not be used continuously to compensate all demands of energy. Thus, the renewable ones must substitute for fossils. Among renewable energies, solar energy was selected as the research topic being a major option. The main reason behind the study is to show an alternative method of creating newgeneration cells. As the content, it was aimed to manufacture a solar cell and, it was achieved for the size of 2x2 cm by the following methods which determined processes as a result of the examinations. P-type silicon was selected as wafer due to its contribution to high total efficiency. After getting this material as p-type, phosphor was determined from 5A group in order to create p-n junction and it was diffused inside in the high temperature levels. Because in only this circumstance, solar energy mobilizes the idle electrons in the material and subsequently, it is provided to fill orbitals where they belong to. After forming p-n junction, anti-reflective coatings (ARC) were implemented to the surface so that much more electrons to flow in the path. Then, the strips were built up the both sides of this mat to complete the equivalent circuit diagram. Consequently, metallization processes ensured to obtain the highest level of voltage. For the up-side, Ag was chosen due to its good value of conductance. During all these processes; XRD, SEM, and Reflectometer machines were used to test the material. According to results, this technique, as separately each section of the study, can clearly be selected as a production method for larger sized solar cells.